Analytical solution to axisymmetric consolidation under surcharge–vacuum–electro-osmosis. Issue 4 (27th April 2019) - Wang, Liujiang; Wang, Yaoming; Liu, Sihong; Xue, Chenyang
Abstract : Surcharge and vacuum preloading combined with electro-osmosis (surcharge–vacuum–electro-osmosis) is a potential method for accelerating the consolidation rate in soil improvement. However, a main limitation of previous analytical solutions on such a technique is the ignorance of the coupled vertical and horizontal water flow, smear effect, well resistance, time-dependent loading and distribution of the additional stress with depth. In this study, an analytical solution is developed with consideration of the aforementioned influencing factors on the consolidation process under surcharge–vacuum–electro-osmosis. The accuracy of the proposed solution is verified using analytical solutions available in previous literature, and a parametric study is then conducted. The result indicates that the surcharge–vacuum–electro-osmosis method can improve the reinforcement effect and shorten the consolidation time. The degree of consolidation will be underestimated if ignoring the vertical flow, and overestimated if ignoring the smear effect and surcharge loading time in the model. However, a decrease in the vacuum degree along the drain has little effect on the consolidation rate. In addition, a decrease in the additional stress along the depth will reduce the final ground settlement but accelerate the consolidation rate. The proposed analytical solution can be applied in the consolidation design under surcharge–vacuum–electro-osmosis with the electric vertical drain used.